Corporate governance, organisational power and disclosure by firms in the United Arab Emirates. (2015) - Hassan, Mostafa Kamal
This study examines the association between corporate governance mechanisms and corporate disclosure in the United Arab Emirates (UAE). Hypotheses based on agency theory and organisational power literature are developed and tested on 85 firms listed in Dubai and Abu Dhabi stock exchanges. The study also runs multiple regression tests on two sub-samples (46 financial firms and 39 non-financial firms) in order to provide a richer analysis for the empirical findings. Overall, the results show that the extent of firms' disclosure is positively associated with the number of board committees, debt finance, firm size and firm profitability, while it is negatively related to CEO power. This study's findings direct policymakers attention to the importance of: the composition of the board, the optimal size of the board, governing the type of knowledge required for board members, and revisiting the level of foreign ownership in UAE firms.